Dari ruang kelas ke ruang sidang: Mengapa budaya otoriter masih subur di tanah demokrasi? - Naipospos, Agung Kasya (Maliki Interdisciplinary Journal, 2026)
Democracy in Indonesia currently faces a significant regression toward procedural authoritarianism, peaking in the consistent disregard for public aspirations within various strategic state policies. This article explores the hypothesis that the national democratic deficit is a direct reflection of an authoritarian culture internalized from the smallest social units, specifically the academic environment through classroom interaction dynamics. Utilizing a descriptive qualitative method, this research effectively dissects how patterns of power dominance, transactional relations, and the systematic silencing of critical voices within student groups replicate macro-level political elite behavior. The analysis integrates critical perspectives on deliberative leadership, elite dominance within the constitutional framework, and the urgent necessity of humanistic education as a vital antithesis to micro-authoritarianism. Results indicate that classrooms often fail as democratic laboratories, transforming instead into miniatures of authoritarianism through normalized group hegemony and the marginalization of meaningful participation. This study concludes that improving national democracy must fundamentally begin with deconstructing authoritarian culture in educational institutions by revitalizing political ethics and strengthening inclusive dialectical spaces. Without a profound educational transformation, universities risk producing authoritarian technocrats who are technically proficient but morally blind to democratic values and human rights.